"Em defesa dos catholicos": Imprensa católica no episcopado de D. Antônio Ferreira Viçoso - Marcella de Sa Brandao (2015)
This dissertation aims to investigate the thought of Don Antonio Ferreira Viçoso, bishop of Mariana, through the newspapers which he published Selecta Catholica and O Romano. We want to understand how these journals would have represented the ideas of that prelate and what the worldview that these printed would have sought to convey to the faithful, his readership, that is, we turn to the intellectuals of the bishop formulations and at the same time for the message contained in the above papers. The study period corresponds to the years 1836-1875, ranging from the publication of the first journal by the end of the episcopate of Don Viçoso. In addition to the newspapers Selecta Catholica and O Romano, as alternative sources, we consulted O Apostolo, a religious newspaper from Rio de Janeiro, the personalcorrespondence of Don Viçoso, pastorals, handwritten documentation of the bishop (notes, sermons, memos), the Cathecismo de Marianna (Marianna and Cathecism) and other sources we deem relevant to the discussion. In the first part, we make an analysis of the context inwhich the character Antonio Ferreira Viçoso is inserted. Will be discussed the padroado, the regalism in Brazil Empire and the conflicts of power and competence between State and Church. In this first part, will also be analyzed the ultramontanism term, presenting the historiographical debate about that thought. In addition, will address some aspects of thebiography of Don Viçoso, bringing factual information about his life in Portugal, his intellectual formation and his actions as bishop of Mariana. Secondly, we will focus on the two phases of the publication of the newspaper Selecta Catholica, from 1836 to 1837, in Rio de Janeiro and later in Mariana, from 1846 to 1847, seeking to understand how the published texts in these newspapers represented the views of Bishop Mariana. Finally, the newspaper O Romano will be analyzed, notably on issues related to education, instruction and catechesis.